HEIDBERGELLA RHINOCEROS SP. N., A POTENTIAL NEW BIOSTRATIGRAPHIC MARKER FROM LATE APTIAN-EARLY ALBIAN MARNE A FUCOIDI (CENTRAL ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
A new planktonic foraminiferal species, Hedbergella rhinoceros, from the Late Aptian to the Early Albian sediments of the Marne a Fucoidi formation (Umbro —Marchean Apennines, central Italy) is described and illustrated.
Keywords: Planktonic Foraminifera; new species; Mid-Cretaceous; Marne a Fucoidi; Umbro-Marchean Apennines.